PENGEMBANGAN OBJEK WISATA CURUG ARGA DESA SUNDAKERTA KECAMATAN CISAYONG KABUPATEN TASIKMALAYA - Dadang Setia Permana; Billy Mazya Fajar Assidiq; Muhammad Hafidh Maulana Rahman; Muhammad Raihan Arfiansyah (Jurnal Pariwisata Tawangmangu, 2026)
This study examines the development of the Curug Arga Waterfall Tourism Object located in Sundakerta Village, Cisayong District, Tasikmalaya Regency. Although the site has strong natural potential, including a waterfall and a forest landscape, its development remains suboptimal due to limited accessibility, inadequate supporting facilities, weak promotional efforts, and the underperformance of local institutions. This research is important for providing a comprehensive understanding of existing field conditions and for formulating appropriate development strategies aligned with sustainable tourism principles. The study employs a qualitative descriptive approach, using in-depth interviews as the primary data source, supported by field observations and literature review. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, following the Miles and Huberman model. The findings show that the weekly control activities, held every Thursday, are not yet comprehensive, while essential facilities such as toilets, signage, resting areas, and photo spots remain insufficient. Promotion relies mainly on word of mouth, limiting the destination's visibility. Based on the 3A theory, Curug Arga demonstrates strengths in attraction but weaknesses in accessibility and amenities. This study concludes that development strategies should include trail improvements, facility enhancements, strengthened digital promotion, institutional reinforcement, and sustainability-based management to increase competitiveness and long-term viability..